Local turns: Queer histories and Brighton's queer communities. Issue 10 (12th September 2019) - Cook, Matt
Abstract: This piece presents one strand of new research from "Queer Beyond London" (QBL), a UK Arts and Humanities Research Council funded project which ran from 2016 to 2018 and sought out the significance of locality to queer identities and communities in the period 1965–2015 via case studies of Brighton, Leeds, Manchester, and Plymouth. The project is part of a (re)turn to the local in queer historical work, and here I review that shift before exemplifying how a focus on specific local contexts in Brighton since the 1980s enriches our understanding of the ways in which queer life was modulated by geographical position, local economy, demographics, local government and policing, and subcultural and cultural reputation. I show especially how the horrific dimensions of the AIDS crisis and the particular shock of Section 28 of the Local Government Act (1988) in this town of historic queer ease reshaped visions and experiences of community there.